Association of serum bilirubin levels with mortality in patients with diabetes initiating chronic hemodialysis: a competing risks analysis of a single-center cohort. Issue 1 (December 2016) - Toya, Kiwako; Babazono, Tetsuya; Murata, Hidekazu; Hanai, Ko; Uchigata, Yasuko
Abstract Background Evidence remains scarce regarding the property of serum bilirubin levels as a prognostic factor for the incidence of mortality in dialysis patients. Here, we aimed to examine the association between serum bilirubin levels and mortality in patients with diabetes initiating hemodialysis. Methods This was a single-center, observational, historical cohort study of 395 Japanese patients with diabetes initiating chronic hemodialysis. There were 98 women and 297 men, and the mean (±SD) age was 61 ± 12 years. Patients were dichotomized at the baseline median level of serum bilirubin (0.3 mg/dL). The endpoints were the incidence of all-cause and cause-specific mortality. Hazard ratios for these endpoints were estimated using the Fine-Gray subdistribution hazard model and cause-specific hazard model because of the presence of competing risks. Results During a median follow-up period of 3.9 years (range; 0.0–10.7 years), there were 83 cases of death, consisting of 39 and 44 cases from atherosclerotic cardiovascular diseases (ASCVDs) and non-ASCVDs, respectively. In the multivariate competing risks analysis, patients with lower bilirubin levels were associated with higher risk of ASCVD-related mortality (subdistribution hazard ratio 3.57, p  = 0.015) but not with non-ASCVD-related mortality (0.83, p  = 0.665) than those with higher bilirubin levels. Analysis treating bilirubin levels as a continuous variable, as well as cause-specific models yielded the similar results. Conclusions Lower serum levels of bilirubin may be predictive of higher risk of ASCVD-related mortality in patients with diabetes initiating chronic hemodialysis. There was no relationship between levels of bilirubin and non-ASCVD-related mortality.